Analisis Etika Keseimbangan di Episentrum Wisata: Menakar Ambang Batas Pemanfaatan Air Tanah di KEK Mandalika demi Keberlanjutan Ekologi - Afansyah Arrahman; Muhammad Sarjan (Mataram University, 2026)
The rapid development of the tourism sector in the Mandalika Special Economic Zone (SEZ) has increased the demand for clean water, which is largely met through the extraction of groundwater using deep boreholes. This situation has the potential to cause ecological imbalances, such as a decline in the groundwater table, a reduction in the flow rate of community wells, and even the risk of seawater intrusion if water use exceeds the environment’s carrying capacity. This study aims to analyze groundwater utilization practices in the Mandalika SEZ from the perspective of the ethics of balance and to formulate directions for sustainable water resource management. The study employs a qualitative method using a descriptive-analytical case study approach, supported by field research and a literature review. Data were analyzed through the interpretation of various empirical findings, regulations, and scientific studies on groundwater management, environmental ethics, and tourism development. The results of the study indicate that the tourism sector’s high dependence on groundwater has placed pressure on the hydrological system, as evidenced by a decline in water availability for the community and an increased risk of environmental degradation. The anthropocentric paradigm, which views water as an economic commodity, is deemed incapable of ensuring ecosystem sustainability. In contrast, the ecocentric approach offers an ethical framework that views groundwater as an integral part of ecological systems, meaning its use must be aligned with the environment’s carrying capacity and storage capacity. This study recommends strengthening groundwater permitting controls, implementing withdrawal limits based on sustainable yield, conserving recharge areas, utilizing rainwater harvesting technologies, and improving water use efficiency in the tourism sector to achieve a balance between economic development and ecological sustainability.